National monitoring of iodine, sodium, and vitamin D status in toddlers and women of childbearing age – results and lessons learned from a pilot study in Norway - Synne Groufh-Jacobsen; Marianne Hope Abel; Anne Lise Brantsæter; Maria Andersson; Haakon E. Meyer; Sigrun Henjum (Food & Nutrition Research, 2023)
Background: Norway is lacking a population-based national monitoring program for iodine, sodium, and vitamin D status. Objective: The aim of this study was to pilot-test a study design for collecting biological samples from a country-representative sample of 2-year-old children and their mothers and to report results for iodine, salt, and vitamin D at baseline, before initiation of salt iodization in Norway. Design: In a cross-sectional study, we recruited 2-year-old children and their mothers during the routine 2-year check-up through 38 randomly selected health clinics in 2021. Spot urine samples were analyzed for iodine, creatinine, and sodium, and dried blood spots from the mothers were analyzed for thyroglobulin (Tg) and 25-hydroxyvitamin D (25(OH)D). Results: We aimed at including 400 mother–child pairs but recruited only 55 pairs. Major challenges were closed health clinics due to the COVID-19 pandemic, lack of motivation of the health personnel to prioritize recruiting, missing information about non-participation, and high workload for participants. The median urinary iodine concentration (UIC) was 123 (95% CI: 76, 228) µg/L in the toddlers and 83 (95% CI: 72, 99) µg/L in the mothers. The median urinary sodium concentration (UNaC) was 62 (95% CI: 37, 91) mmol/L in the toddlers and 93 (95% CI: 77, 107) mmol/L in the mothers. Of the mothers, 18% had levels of 25(OH)D <50 nmol/L (suboptimal status). Discussion and conclusion: Lessons learned from the pilot study will be used to design a national monitoring program for toddlers and women of childbearing age in Norway. The results indicate that 2-year-old children and women of childbearing age in Norway may have inadequate iodine intakes at the group level, while for vitamin D, most of the mothers had adequate status.